From Tactical Utility to Human Cost: The Normative Shift in the Prohibition of Combatant Suffering - Jaroslav Krasny (Journal for Peace and Nuclear Disarmament, 2025)
This article examines the evolving interpretation of the principle prohibiting superfluous injury or unnecessary suffering in international humanitarian law (IHL) applicable to combatants. Traditionally understood through a military necessity lens, this principle has undergone a normative transformation toward an effects-based interpretation centered on long-term, irreversible and severe health consequences. Tracing its development from the St. Petersburg Declaration of 1868 to the Treaty on the Prohibition of Nuclear Weapons (TPNW), the article highlights key milestones including the Vietnam War, the International Court of Justice (ICJ) Advisory Opinion on nuclear weapons, and the International Committee of the Red Cross (ICRC)’s SIrUS project. Drawing on legal texts, judicial opinions, and testimonies of affected combatants, it argues that the balance between military advantage and suffering has tilted decisively in favor of humanitarian constraints. While not formally codified, this metamorphosis is reflected in disarmament treaties that prioritize health outcomes over combat utility. The article concludes that with the rise of humanitarian disarmament, the principle of unnecessary suffering is increasingly interpreted as prohibiting weapons whose long-term health effects cannot be justified by military necessity – a shift that will become more pronounced as new technologies emerge.